Reducing Economics Test Anxiety among Students as Measured by a Test Anxiety Scale: A Cognitive Behavioural Therapy - Amedu, Amos Nnaemeka (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
Psychological problems such as anxiety have been reported to adversely affect students' learning outcomes. This study explored the effectiveness of cognitive therapy with reflective activities on reducing Economics test anxiety among secondary school students. A randomizedcontrolledtrial experimental design was used. The sample sizewas120 senior secondary school students in South East Nigeria.A questionnaire titled